Modules with respect to cyclic purity - Mao, Lixin (Mathematica Scandinavica, 2011)
An exact sequence 0→ A→ B→ C→ 0 of left R-modules is called cyclically pure if for every right ideal I of R, the sequence 0→ (R/I)A → (R/I)B → (R/I)C → 0 is exact. In this paper, we study some special modules with respect to cyclic purity, such as CP-projective, CP-injective and CP-flat modules.